Clinical utility of circulating tumor DNA sequencing in advanced gastrointestinal cancer: SCRUM-Japan GI-SCREEN and GOZILA studies - Nakamura, Yoshiaki; Taniguchi, Hiroya; Ikeda, Masafumi; Bando, Hideaki; Kato, Ken; Morizane, Chigusa; Esaki, Taito; Komatsu, Yoshito; Kawamoto, Yasuyuki; Takahashi, Naoki; Ueno, Makoto; Kagawa, Yoshinori; et al. (Nature medicine, 2020)
Comprehensive genomic profiling enables genomic biomarker detection in advanced solid tumors. Here, to evaluate the utility of circulating tumor DNA (ctDNA) genotyping, we compare trial enrollment using ctDNA sequencing in 1,687 patients with advanced gastrointestinal (GI) cancer in SCRUM-Japan GOZILA (no. UMIN000016343), an observational ctDNA-based screening study, to enrollment using tumor tissue sequencing in the same centers and network (GI-SCREEN, 5,621 patients). ctDNA genotyping significantly shortened the screening duration (11 versus 33 days, P < 0.0001) and improved the trial enrollment rate (9.5 versus 4.1%, P < 0.0001) without compromising treatment efficacy compared to tissue genotyping. We also describe the clonal architecture of ctDNA profiles in ~2,000 patients with advanced GI cancer, which reinforces the relevance of many targetable oncogenic drivers and highlights multiple new drivers as candidates for clinical development. ctDNA genotyping has the potential to accelerate innovation in precision medicine and its delivery to individual patients. An observational study on a large cohort of patients with gastrointestinal cancer demonstrates the utility of ctDNA analysis for accelerating the enrollment of patients in clinical trials with no accompanying deterioration in treatment efficacy.